Impact of different standard red blood cell storage temperatures on human and canine RBC hemolysis and chromium survival. Issue 1 (1st November 2018) - Blaine, Kevin P.; Cortés‐Puch, Irene; Sun, Junfeng; Wang, Dong; Solomon, Steven B.; Feng, Jing; Gladwin, Mark T.; Kim‐Shapiro, Daniel B.; Basu, Swati; Perlegas, Andreas; West, Kamille; Klein, Harvey G.; et al.
Abstract : BACKGROUND: Storage temperature is a critical factor for maintaining red‐blood cell (RBC) viability, especially during prolonged cold storage. The target range of 1 to 6°C was established decades ago and may no longer be optimal for current blood‐banking practices. STUDY DESIGN AND METHODS: Human and canine RBCs were collected under standard conditions and stored in precision‐controlled refrigerators at 2°C, 4°C, or 6°C. RESULTS: During 42‐day storage, human and canine RBCs showed progressive increases in supernatant non–transferrin‐bound iron, cell‐free hemoglobin, base deficit, and lactate levels that were overall greater at 6°C and 4°C than at 2°C. Animals transfused with 7‐day‐old RBCs had similar plasma cell‐free hemoglobin and non–transferrin‐bound iron levels at 1 to 72 hours for all three temperature conditions by chromium‐51 recovery analysis. However, animals transfused with 35‐day‐old RBCs stored at higher temperatures developed plasma elevations in non–transferrin‐bound iron and cell‐free hemoglobin at 24 and 72 hours. Despite apparent impaired 35‐day storage at 4°C and 6°C compared to 2°C, posttransfusion chromium‐51 recovery at 24 hours was superior at higher temperatures. This finding was confounded by a preparation artifact related to an interaction between temperature and storage duration that leads to removal of fragile cells with repeated washing of the radiolabeled RBC test sample and renders the test sample unrepresentative of the stored unit. CONCLUSIONS: RBCs stored at the lower bounds of the temperature range are less metabolically active and produce less anaerobic acidosis and hemolysis, leading to a more suitable transfusion product. The higher refrigeration temperatures are not optimal during extended RBC storage and may confound chromium viability studies.